2021
DOI: 10.1002/jhbp.966
|View full text |Cite
|
Sign up to set email alerts
|

A novel laser‐cut fully covered metal stent with anti‐reflux valve in patients with malignant distal biliary obstruction refractory to conventional covered metal stent

Abstract: Distal malignant biliary obstruction (MBO) is often caused by pancreatic cancer, biliary tract cancer, and lymph node metastasis. Endoscopic placement of a self-expandable metal stent (SEMS) is the standard treatment for unresectable distal MBO due to the long stent patency compared to plastic stents. [1][2][3] There are two types of SEMS: uncovered SEMS (UMS) and covered SEMS (CMS). Recent meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…Recent reports from Japan have described the usefulness of this stent. [26][27][28][29][30] In the one case of RBO caused by sludge formation in the present study, the check valve had collapsed. Kin et al reported RBO due to sludge formation in five patients, of whom the check valve had collapsed in two.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Recent reports from Japan have described the usefulness of this stent. [26][27][28][29][30] In the one case of RBO caused by sludge formation in the present study, the check valve had collapsed. Kin et al reported RBO due to sludge formation in five patients, of whom the check valve had collapsed in two.…”
Section: Discussionmentioning
confidence: 47%
“…Kin et al reported RBO due to sludge formation in five patients, of whom the check valve had collapsed in two 27 . Yamada et al reported RBO caused by sludge formation or non‐occlusion cholangitis in five cases, and the check valve had collapsed in all five 30 . As it is expected that failure of the check valve will cause sludge formation and subsequent RBO, it is desirable to improve the durability of the check valve in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovered SEMS is usually difficult to remove due to the growth of hyperplastic tissue into the stent 1 . FC‐SEMS may avoid this embarrassing event and novel laser‐cut covered self‐expandable metallic stents may be more effective 2,3 . Successful removal of biliary uncovered SEMS that have been placed for up to 15 years is rare and also meaningful.…”
Section: Figurementioning
confidence: 99%
“…1 FC-SEMS may avoid this embarrassing event and novel laser-cut covered self-expandable metallic stents may be more effective. 2,3 Successful removal of biliary uncovered SEMS that have been placed for up to 15 years is rare and also meaningful. The "stent-in-stent" technique is to be feasible in SEMS removal.…”
mentioning
confidence: 99%